The Italian Hall tragedy, 1913: A hundred years of remediated memories. - Anne Heimo (Brill, 2022)
The Italian Hall tragedy, 1913: A hundred years of remediated memories
On Christmas Eve 1913 seventy-three people were crushed to death during the 1913–1914 Copper Strike in the small township of Calumet on the Keweenaw Peninsula, Upper Michigan. On Christmas Eve the local Women's Auxiliary of the Western Federation of Miners (WFM) had arranged a party for the strikers’ families at the local Italian hall. At some point in the evening someone was heard to shout “fire” and as people rushed to get out of the building they were hauled down the stairs and were crushed to death. Sixty-three of the victims were children. There was no fire. Later on this tragic event became to be known as “The Italian hall tragedy”, “The Italian Hall Disaster” or the “1913 Massacre” and it continues to be the one most haunting event in the history of the Copper Country.
The Twentieth Century in European Memory: Transcultural mediation and reception